Acid Black 48 dye biosorption using Saccharomyces cerevisiae immobilized with treated sugarcane bagasse - Mitter, E. K. [UNESP]; Corso, C. R. [UNESP] (I W A Publishing, 2012)
The textile industry consumes large quantities of water and chemicals, especially in dyeing and finishing processes. Textile dye adsorption can be accomplished with natural or synthetic compounds. Cell immobilization using biomaterials allows the reduction of toxicity and mechanical resistance and opens spaces within the matrix for cell growth. The use of natural materials, such as sugarcane bagasse, is promising due to the low costs involved. The aim of the present study was to evaluate the use of sugarcane bagasse treated with either polyethyleneimine (PEI), NaOH or distilled water in the cell immobilization of Saccharomyces cerevisiae for textile dye removal. Three different adsorption tests were conducted: treated sugarcane bagasse alone, free yeast cells and bagasse-immobilized yeast cells. Yeast immobilization was 31.34% with PEI-treated bagasse, 8.56% with distilled water and 22.54% with NaOH. PEI-treated bagasse exhibited the best removal rates of the dye at all pH values studied (2.50, 4.50 and 6.50). The best Acid Black 48 adsorption rates were obtained with use of free yeast cells. At pH 2.50, 1 mg of free yeast cells was able to remove 5488.49 g of the dye. The lowest adsorption capacity rates were obtained using treated bagasse alone. However, the use of bagasse-immobilized cells increased adsorption efficiency from 20 to 40%. The use of immobilized cells in textile dye removal is very attractive due to adsorbed dye precipitation, which eliminates the industrial need for centrifugation processes. Dye adsorption using only yeast cells or sugarcane bagasse requires separation methods.
Keywords: immobilization; polyethyleneimine; Saccharomyces cerevisiae; sugarcane bagasse; textile dyes